The therapeutic effect of PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres combined with magnetic fluid hyperthermia on hepatoma - Zhang, Hao; Li, Suping; Chen, Fei; Ma, Xingming; Liu, Mingying (Frontiers in Oncology, 2023)
Background Hepatocellular carcinoma (HCC) is one of the most prevalent and deadly malignant tumors with serious clinical and socioeconomic consequences. Although gene therapy holds great promise in the treatment of hepatoma, its clinical applications are hindered by uncontrolled gene transmission and transcription. Methods The pY-ads-8-5HRE-cfosp-IFNG plasmid was constructed and identified by double enzyme digestion and gene sequencing. The expression of pYr-ads-8-5HRE-cfosp-IFNG in HepG2 cells was detected by quantitative PCR. PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres were prepared and characterized. In vitro heating test of magnetic albumin nanospheres in an alternating magnetic field (AMF) was carried out. The therapeutic effect of PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres on hepatocellular carcinoma was investigated by cell and animal experiments. After treatment, mice blood was collected for clinical biochemical analysis and histopathological evaluation of major organs was performed to assess potential adverse effects of treatment. Results Double enzyme digestion and gene sequencing showed that the pY-ads-8-5HRE-cfosp-IFNG plasmid was constructed successfully. QPCR results showed that the IFNγ transcript level in the PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG group was higher than that in the PEI-Fe3O4/pYr-ads-8-cfosp-IFNG group after being treated with hypoxia (P<0.05). TEM revealed that the self-prepared PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres exhibit an approximately spherical or elliptical shape. The hydrodynamic size of the albumin nanospheres was 139.7 nm. The maximum temperature of 0.25 mg/mL solution is stable at about 44°C, which is suitable for tumor thermal therapy without damaging normal tissues. The relative cell inhibition rate of the radiation-gene therapy and MFH combination group was higher than that of other control groups in CCK8 experiment. (P<0.05) Flow cytometry showed that the apoptosis rate and necrosis rate of the combined treatment group were 42.32% and 35.73%, respectively, higher than those of the other groups. (P<0.05) In animal experiments, the mass and volume inhibition rates of the combined treatment group were 66.67% and 72.53%, respectively, higher than those of other control groups. (P<0.05) Clinical biochemical analysis and histopathological evaluation showed no abnormality. Conclusions The results indicated the successful construction of the radiation-induced plasmid and demonstrated that the hypoxia enhancer could augment the expression of INFγ in a hypoxia environment. Gene therapy combined with magnetic fluid hyperthermia (MFH) has exhibited excellent outcomes in both cell and animal studies. Our experiments demonstrated that the PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres system is a comprehensive treatment method for hepatoma, which can effectively combine immune genre therapy with hyperthermia.